O (dez)iluzji oraz drogach i bezdrożach przeznaczenia w "Ofierze królewny" Jana Lemańskiego - Ratuszna, Hanna (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2017)
The article analyses the phenomenon of identity crisis in a “modern man” (“at the threshold of modernity”). Lemański employs a fairy-tale convention, the result, however, is an anti-fairy-tale (to use Anna Czabanowska – Wróbel’s term). Irony, laughter or grotesque elements suggest that the literary intention of the author of Bajki was an interesting commentary on reality (critics, including Zenon Przesmycki, pointed the renaissance of fairy tales found in modernist literature). Lemański’s work is characterised by a somewhat careless approach to the form, which becomes the principle describing the world represented. The theme of destiny, the topos of wandering as well as initiation themes match the fairy-tale convention, albeit processed in an interesting way.